2017
DOI: 10.1002/cpt.927
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy in Ischemic Stroke: A Meta‐analysis of Preclinical Studies

Abstract: Numerous preclinical studies have been carried out using mesenchymal stem cells (MSCs) therapy for ischemic stroke. The purpose of the present meta-analysis is to review the quality of preclinical studies. In all, 4,361 articles were identified, out of which 64 studies were included (excluding in vitro studies). The results were obtained across species, route, and time of administration, immunogenicity, and doses. The median quality score 4.90/10, confidence interval 95%, and large effect size were observed, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 77 publications
0
43
0
1
Order By: Relevance
“…23 A recent meta-analysis of preclinical studies of MSCs in ischemic stroke showed that MSCs were infused either immediately or over a period varying from 24 hours to 4 weeks; none of the 64 publications used an 8-week post-MCAO MSC administration time. 25 In our stroke model, we obtained T2-weighted images 8 weeks after MCAO and excluded rats with infarcted volumes smaller than 230 mm 3 . H & E staining of brain sections from animals killed at 8 weeks after MCAO induction also indicated a chronic stage of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent meta-analysis of preclinical studies of MSCs in ischemic stroke showed that MSCs were infused either immediately or over a period varying from 24 hours to 4 weeks; none of the 64 publications used an 8-week post-MCAO MSC administration time. 25 In our stroke model, we obtained T2-weighted images 8 weeks after MCAO and excluded rats with infarcted volumes smaller than 230 mm 3 . H & E staining of brain sections from animals killed at 8 weeks after MCAO induction also indicated a chronic stage of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of MSCs is associated with their ability to moderate the regenerative niche in a wound site, which commonly involves an ischemic environment (Bhang et al, 2011;Chen et al, 2016;Sarmah et al, 2018). This study observed that both bMSCs and ASCs showed significantly increased survival following 3D aggregation in the ischemic environment, while the opposite effect was seen in FB.…”
Section: Isr Helps Manage Environmental Stressors and Extends Stem mentioning
confidence: 83%
“…Терапевтические эффекты МСК были широко исследованы в экспериментальных работах [33,34,[36][37][38] на животных моделях ишемии головного мозга. Было показано, что трансплантация МСК уменьшает моторный дефицит и улучшает выполнение поведенческих тестов.…”
Section: нскunclassified